CLASSIFICATION OF INTRAVENTRICULAR HEMORRHAGE IN NEWBORNS IN THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES - Vasily V. Vlasyuk ("Paediatrician" Publishers LLC, 2017)
The article presents the classification of intraventricular hemorrhages  (IVH) contained in the International Statistical Classification of Diseases and Related Health Problems (ICD), the 10th revision. The classification of IVH developed over 30 years ago is now obsolete. The contradictions discovered in the classification of IVH are considered. The neurosonographic basis of this classification is underlined and its morphological variant is proposed, which should become the basic one for both neuroimaging and for all clinical diagnostics. Based on the analysis, it was suggested to exclude any classification of IVC from the ICD of a new revision.